The genesis of contemporary economic theory, by Alexander Tobón Arias - Timothey Vitu (Lecturas de Economía, 2023)
Is economic theory still useful today? In a new book, Alexander Tobón Arias answers that question (I’ll come back to this at the end) as he presents and attempts to promote the history of economic theory. The author was motivated to write this book by a “growing contempt of many economists for economic theory” in favor of applied economics. The synthesis he proposes aims to shed light on theoretical economics.